The Effect of Ethical Climate and Job Satisfaction on Turnover Intention Mediated by Organizational Commitment - Nugroho, Farid Irawan; Muafi, Muafi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
This study aims to examine and analyze the effect of ethical climate and job satisfaction on turnover intention mediated by organizational commitment at DN Production, Yogyakarta. The population in this study was 35 people with the sampling technique using the census method. This research uses quantitative methods by distributing questionnaires to employees. The analytical test tool used is Smarts v.3.0 with SEM (Structural Equation Modelling) analysis method. The results of data analysis in this study indicate that ethical climate has a negative effect on turnover intention, job satisfaction has a negative effect on turnover intention, the ethical climate has a positive effect on organizational commitment. , job satisfaction has a positive effect on organizational commitment, organizational commitment has a negative effect on turnover intention, organizational commitment indirectly mediates ethical climate on turnover intention, organizational commitment has a mediating role on job satisfaction on turnover intention.